1990
DOI: 10.1530/acta.0.1230194
|View full text |Cite
|
Sign up to set email alerts
|

Renal tubular reabsorption of calcium and sodium in primary hyperparathyroidism

Abstract: Nine patients with primary hyperparathyroidism were studied to investigate the renal tubular reabsorption of calcium and sodium. Fasting serum and urine samples were analysed, and the glomerular filtration rate and the renal plasma clearance of lithium were determined simultaneously. Comparison was made with 9 ageand sex-matched normocalcemic controls. In the proximal tubule, there was a significantly higher absolute reabsorption of calcium in patients than in controls, whereas the fractional reabsorption rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Others have found that urinary calcium excretion factored by GFR is low in HPT vs NS when plotted against serum calcium or ultrafilterable calcium; this implies a lower FECa in HPT than in NS, and is opposite to what we found. However, serum calcium values of NS did not overlap with HPT, so such a comparison requires either that normal serum calcium values are extrapolated to the high levels in HPT using a regression equation [13], or as we did previously [3], use studies of NS rendered hypercalcaemic by calcium infusion, or be content to calculate FECa from actual values, as in the present study. We think that the last of the three is most useful because it returns a value of FECa that actually applies to the persons under question, whereas the other two relate to conditions that are in fact theoretical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have found that urinary calcium excretion factored by GFR is low in HPT vs NS when plotted against serum calcium or ultrafilterable calcium; this implies a lower FECa in HPT than in NS, and is opposite to what we found. However, serum calcium values of NS did not overlap with HPT, so such a comparison requires either that normal serum calcium values are extrapolated to the high levels in HPT using a regression equation [13], or as we did previously [3], use studies of NS rendered hypercalcaemic by calcium infusion, or be content to calculate FECa from actual values, as in the present study. We think that the last of the three is most useful because it returns a value of FECa that actually applies to the persons under question, whereas the other two relate to conditions that are in fact theoretical.…”
Section: Discussionmentioning
confidence: 99%
“…Kristiansen et al. [13], using graphical extrapolation, concluded that the FECa of HPT was below that of NS. However, using their data, we conclude otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…PTH regulates reabsorption of the 10% of filtered Ca that reaches the DCT by controlling expression of the apical calcium channel transient receptor potential vanilloid 5 (TRPV5), the intracellular transporter calbindin-D 28K , and the basolateral extrusion proteins sodium-calcium exchanger 1 (NCX1) and plasma membrane calcium ATPase 1b (PMCA1b) [ 10 , 11 , 30 ]. In primary hyperparathyroidism (PHPT), elevated [PTH] causes hypercalcemia by increasing TR Ca /C cr [ 12 , 49 ]; in SHPT, comparable or higher [PTH] is associated with and presumably required to achieve normal TR Ca /C cr and normocalcemia [ 12 ]. This presumption is consistent with the observation that cinacalcet, a calcimimetic that suppresses synthesis and secretion of PTH, reduced tubular Ca reabsorption and caused hypocalcemia as it lowered [PTH] in CKD stages G 3 and G 4 [ 50 ].…”
Section: Discussionmentioning
confidence: 99%